1991
DOI: 10.1002/ijc.2910470612
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study on stomach cancer in Germany

Abstract: A multicentric hospital-based case-control study was simultaneously performed in a high-risk and a low-risk area for stomach cancer in Germany, 143 patients with incident stomach cancer and 579 controls completing a retrospective interview about life style aspects. Periods of non-centralized water supply or well water as the only source compared to life-long central water supply, and preservation of meat by smoking it with spruce compared to no home smoking of meat, were significantly associated with an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
3
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(108 citation statements)
references
References 23 publications
4
95
3
4
Order By: Relevance
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 66%
“…Overall, in the majority of case-control studies, positive associations were observed for (total) salt or sodium intake [2,3,33,34], consumption of salted fish, salted meat, pickles and soup [5,7,16,[34][35][36][37][38][39][40], adding salt to food at dinner [5,9,41], preference of salty foods [4,5,11,40,42]. The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many case-control studies of gastric or esophageal cancer have previously found inverse associations with vegetable and fruit consumption, [27][28][29] but the evidence from prospective cohort studies has been inconsistent. [30][31][32] In our prospective study, neither vegetable nor fruit consumption, nor intake of antioxidant vitamins usually contained in vegetables and fruit, was associated with the risk of upper digestive tract cancer.…”
Section: Discussionmentioning
confidence: 99%